Variation of Saturation Across Hue Affects Unique and Typical Hue Choices. (September 2019) - Witzel, Christoph
Most studies on colour categorisation and many studies on unique hues have used samples of maximally saturated Munsell chips that vary in saturation across hue. Here we show that observers' choices of category prototypes and unique hues depend on the variation of Munsell chroma across hue. Both unique hue and prototype choices were shifted towards the more saturated hues in the respective stimulus set. This effect of saturation may explain cross-cultural regularities in colour categorisation. More generally, these findings highlight the importance of controlling saturation when measuring colour categories and unique hues.